Measuring Social Impact: an analysis of Sustainable Startups (European journal of volunteering and community-based projects, 2025)
PurposeThis study investigates how sustainable startups use the Social Return on Investment (SROI) framework to assess and communicate their social value. It aims to explore the advantages and limitations of SROI in early-stage entrepreneurial contexts.Design/methodology/approachA qualitative methodology was adopted through a literature review, expert interviews, and two in-depth case studies. These include startups operating in the sustainable innovation space and one accelerator programme. Data were analysed to assess how SROI is applied and its influence on strategic management.FindingsThe findings reveal that SROI supports sustainable startups in legitimizing their social mission, attracting impact-oriented investors, and structuring their value proposition. However, challenges arise due to limited resources, methodological complexity, and evolving business models.Research limitations/implicationsThis study is limited by the small sample size and the exploratory nature of the qualitative analysis. Further research with larger samples and quantitative methods is suggested.Practical implicationsThe paper offers insights for entrepreneurs, investors, and policymakers seeking to integrate social impact measurement into startup strategy and funding practices.Originality/valueThis research contributes to the emerging field of impact measurement in sustainable entrepreneurship. It proposes the SROI framework as a practical yet adaptable method for early-stage ventures to quantify and communicate their broader societal contributions.